Automated isochronal late activation mapping to identify deceleration zones: Rationale and methodology of a practical electroanatomic mapping approach for ventricular tachycardia ablation. (1st November 2018) - Raiman, Michael; Tung, Roderick
Abstract: Sinus rhythm surrogates for critical isthmus sites are highly desirable because the vast majority of VT is hemodynamically unstable. While many ablation strategies to decrease the arrhythmogenicity of scar have been shown to be effective, the predominant method for electroanatomic mapping relies on a voltage-based depiction of scar and abnormal electrograms. A functional prioritization of slow conduction, distinct from late activation, is feasible in clinical practice with the creation of isochronal late activation maps. Regions of slow conduction are easily visualized with isochronal displays of baseline intrinsic rhythm activation and deceleration zones, where isochrones crowd, have been observed to have strong correlation with successful ablation sites. Automated annotation of the offset of local electrograms was developed to create the propagation maps to incorporate electrogram width and completion of local activation. Simple conduction velocity estimates where three isochrones are seen within a 1 cm radium confirm that deceleration zones harbor conduction velocity of <0.6 m/s. We present a practical methodology of analyzing electroanatomic substrate in a voltage-independent manner with correlation to reentrant VT. Non-linear 3D transmyocardial conduction limits the validity of conduction velocity estimates that assume planar and tangential conduction and we show an example of a patient with 3D isthmus boundaries with an activation gap on the epicardial surface during tachycardia. Highlights: Functional analysis of activation patterns hold promise to identify arrhythmogenic regions within scar. Where abrupt slowing of conduction velocities ca be visualized as isochronal crowding. Quantification of deceleration zone by a clinically practical method of identifying areas with 3 colors within 1 cm appears to correlate with conduction velocities <0.6 m/s in humans. Conduction velocity estimates typically assume a linear path, which oversimplifies transmyocardial 3D activation.